IFSA 2013: commentaries on Islamic banking and finance - Lee, Mohd Johan; Oseni, Umar Aimhanosi (Malaysian Current Law Journal Sdn. Bhd., 2015)
The enactment of the Islamic Financial Services Act 2013 (IFSA 2013) has marked an exceptional milestone in the development of the domestic Islamic financial services industry. With an initial unprecedented legislation and enviable practices in the industry created over 30 years, Malaysia has yet again pioneered the enabling legislative reforms vital for industry fluidity and harmonisation of laws relating to the financial services. While the Act caters to all regulatory and supervisory aspects of the industry, this book aims to provide a succinct commentary of the provisions within the Islamic Banking parameters. As the nature of legislative commands changes from detailed and prescriptive approach to one which is principle-based, this book provides a perfect companion to assist readers in understanding and navigating through the current legislative maze. Special features of the book: • Concise yet comprehensive commentary of the main provisions with accompanying regulatory guidelines • Clearly structured analyses for better understanding of the industry requirements • Comprehensive coverage on Islamic banking industry, including the Shariah requirements, powers and functions of Bank Negara, consumer protection, business conducts, as well as enforcement and penalties by Bank Negara • Discussion on the introduction of the Financial Ombudsman Scheme and arbitration in Islamic finance disputes. • A quick reference guide suitable for legal practitioners, bankers and other industry players; as well as an essential reading for academicians and students of Islamic banking.